Mixed acinar-endocrine carcinoma of pancreas: A case report and brief review of the literature - Liu, Zhenzhen (Onco Targets Ther, 2015)
Mixed acinar-endocrine carcinoma (MAEC) of the pancreas is a rare entity. We present a 65-year-old Chinese female who was admitted with jaundice and nagging epigastric pain with intermittent diarrhea for 1 month. She eventually underwent abdominal magnetic resonance imaging, which showed an 8×6 cm mass in the head of the pancreas and showed two abnormal lesions in the liver simultaneously. MAEC of the pancreas with synchronous hepatic metastasis was confirmed with immunohistochemistry after Whipple operation and hepatic partial resection of the lesions. Postoperative recovery of this patient was uneventful, and no evidence of recurrence or metastasis was observed after 12 months of follow-up. MAEC of pancreas is thought to be extremely rare and lack of typical clinical symptoms. The prognosis is poor overall, but early detection with complete resection may be beneficial to patients.